Understanding the molecular basis of NO-releasing β-cyclodextrin derivatives and ferulic acid co-delivery for advanced therapeutics: A theoretical study - Ji Mu; Meiqi Ni; Wei Dong; Chaojie Wang; Yuting Luo; Kun Wang (Carbohydrate Polymer Technologies and Applications)
The molecular dynamics (MD) simulations and density functional theory (DFT) calculations were employed to examine the structural stability and intricate interplay of supramolecular complexes formed between ferulic acid (FA) and β-cyclodextrins (β-CD), as well as its nitric oxide (NO)-releasing derivatives: N-diazeniumdiolate-modified β-CD-ethylenediamine (E-β-CD) and N-diazeniumdiolate-modified β-CD-diethylenetriamine (D-β-CD). The results indicated that FA adopted two stable orientations within the hydrophobic cavity of various β-CDs, namely carboxyl group insertion (Conf-Ca) and phenyl group insertion (Conf-Ph), primarily driven by the van der Waals forces. Subsequently, 500-ns MD simulations performed on these inclusion complexes demonstrated the improved encapsulation efficacy and robust structural stability for FA@E-β-CD and FA@D-β-CD. Analysis of the interaction energies and energy decomposition on the DFT-optimized structures confirmed that these complexes in Conf-Ph exhibited stronger binding affinity to FA than those in Conf-Ca. Furthermore, the independent gradient model based on Hirshfeld partition (IGMH) and electrostatic potential (ESP) analysis corroborated that the enhanced affinity stemmed from the extensive dispersion interactions and strong hydrogen bonds between the β-CD derivatives and FA. The findings provide fundamental knowledge on the molecular structure and interactions of these complexes, thereby facilitating the development of advanced therapeutic gas and drug co-delivery systems based on NO-releasing β-CD derivatives.